2014
DOI: 10.1016/s2213-2600(14)70017-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated obstructive lung diseases: insights and implications for the clinician

Abstract: The effectiveness of antiretroviral therapy to control HIV infection has led to the emergence of an older HIV population who are at risk of chronic diseases. Through a comprehensive search of major databases, this Review summarises information about the associations between chronic obstructive pulmonary disease (COPD), asthma, and HIV infection. Asthma and COPD are more prevalent in HIV-infected populations; 16–20% of individuals with HIV infection have asthma or COPD, and poorly controlled HIV infection worse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 67 publications
(104 reference statements)
1
54
0
8
Order By: Relevance
“…These drugs, with a "class effect" (amphetamine-like) or not (dasatinib), are prescribed for serious (dasatinib, interferons) or moderate (benfluorex) pathologies and do not induce PAH in all patients [1][2][3][4][5][6][7][8][9]. As a result, assessment of drug history exposure from PAH patients has become essential for providing optimal disease management [10].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs, with a "class effect" (amphetamine-like) or not (dasatinib), are prescribed for serious (dasatinib, interferons) or moderate (benfluorex) pathologies and do not induce PAH in all patients [1][2][3][4][5][6][7][8][9]. As a result, assessment of drug history exposure from PAH patients has become essential for providing optimal disease management [10].…”
Section: To the Editormentioning
confidence: 99%
“…Studies in the USA have found that 16-20% of HIV-positive individuals have asthma or chronic obstructive pulmonary disease (COPD), and poorly controlled HIV accelerates lung function decline [1]. In HIV-negative patients with COPD, one report identified lower airway bacterial colonisation (LABC) in 44% of stable-state COPD patients, and found it to be associated with increasing airway inflammation, frequency of exacerbations and lung function decline [7].…”
mentioning
confidence: 99%
“…In this regard, select HIV-infected individuals who smoke cigarettes develop accelerated chronic obstructive pulmonary disease (COPD) through mechanisms that are incompletely understood (1)(2)(3)(4). However, the roles of HIV and host immunity in HIV-associated COPD remain poorly understood.…”
Section: Copdmentioning
confidence: 99%
“…PI treatments (for example, ritonavir) can result in systemic accumulation of inhaled corticosteroids and may increase the risk of pneumonia by exacerbating the toxicity of this treatment in HIV-infected inhabitants with asthma or chronic obstructive pulmonary disease (25).…”
Section: Bacterial Pneumoniamentioning
confidence: 99%